Pedagogy and cognitive neurosciences in dialog. The example of bodily experience - Francesconi, Denis (Formazione & insegnamento, 2015)
The education sciences and cognitive sciences are gaining more ground in common (Fischer, Daniel, Immordino-Yang, Stern, Battro, Koizumi 2007), not only to the classical themes of learning, memory, attention and language but also to the themes of consciousness and the body. Indeed, an interesting and unexpected new paradigm of theoretical and empirical research that was born 20 years ago is now connecting the old philosophical tradition of phenomenology and the cognitive sciences, with a special attention to the role of the body in the process of constitution of the mind and identity (Cappuccio 2006; Gallagher 2005). That paradigm is the so-called embodied theory. In this article, the practices of meditation and mindfulness meditation are discussed as good examples of experiential education that can be scientifically studied and practically applied within the educational field following the embodied perspective.